The Principle of Independence of the Notary as a General Officer in Cooperation Agreements with Private Banks - Semadi, I Komang Yoga; Nurjaya, I Nyoman; Sulistyarini, Rachmi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This thesis is entitled "Principles of Independence as a General Officer in Cooperation Agreements with Private Banks" with 3 (three) main issues, namely: (1) What is the meaning of the Notary's Independence in exercising his authority as a Public Official based on Article 16 paragraph (1) letter a UUJN? (2) How is the urgency of the regulation related to the meaning of the Notary's Independence in carrying out his authority as a Public Official? (3) Is the “first party interest” clause in the cooperation agreement with Private Banks part of the notary independence? This research is a type of legal research with normative juridical research methods. Besides, this research uses a statutory approach and a conceptual approach. The results of this thesis research indicate that the independence of a notary can be interpreted as a notary must work properly and professionally according to the provisions of the legislation without any influence and coercion from other parties. The urgency of this meaning of Notary independence is to create legal certainty and facilitate the determination of sanctions to Notaries who violate the principle of Notary independence. The urgency of the meaning of the principle of independence of a Notary is to provide legal certainty.